ANALYSIS OF LIQUIDITY IN PT. BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, TBK. USING THE CASH RASIO METHOD - Alawiyah, Nadilatul; Suryani, Emma; Utami, Fiesty; Agusetiawan Shavab, Firli (Management Science Research Journal, 2024)
In checking the health of a bank, each bank must pay attention to the level of liquidity. Liquidity is the ability of an organization to pay its short-term debt quickly. This cash ratio shows the bank's ability to repay depositors or client savings when withdrawn with its liquid assets. To determine a business's ability to meet its current debt obligations, calculations using the debt ratio are very important. The aim of this research is to determine the level of liquidity of PT. Regional Development of West Java and Banten, Tbk. using the money ratio method from 2019 to 2021. This research uses a quantitative descriptive approach. In 2019, 2020 and 2021 the liquidity value of PT. Regional Development of West Java and Banten, Tbk exceeded 4.05% (based on the predicate health ratio indicator by the Board of Directors of Bank Indonesia) so that there are no obstacles to fulfilling its current obligations.